Population Structure of Alstonia scholaris (L) R.Br in The Region of Bajuin Waterfall Tanah Laut - Heri Setiono; Dharmono Dharmono; Muchyar Muchyar (Universitas Sebelas Maret, 2015)
Alstonia scholaris (L) R.Br is one useful plant species in region South Borneo especially in the bajuin waterfall areas. According to local people, Alstonia scholaris (L) R.Br diminishing numbers. Determining the status or situation in a habitat can be done by studying the population structure. It is very important to be done in an effort to perform against the preservation of the population. The purpose of this research is to review the population structure of Alstonia scholaris (L) R.Br in the region of bajuin waterfall Tanah Laut. The method used in this research is survey 10 m x 10 m quadrant for the seeedling, sapling, pole and tree, systematically on two regions above and below waterfall each 500 m x 250 m quadrant. The results showed that the population structure of Alstonia scholaris (L) R.Br in one region there is a number of trees 56 individual/ha, the pole 28 individuals/ha, sapling 16 individuals/ha and seedling 8 individuals/ha, whereas the second region there are number tree 80 individuals/ha, the pole 52 individuals/ha, sapling 76 individuals/ha and seedling 48 individuasl/ha . In both regions show a number lot of the adult age group which means the plants in a state of decline or threated and obtained a description of the shape of a pyramid population structure shape urn that is disturbed.Keywords: Population Structure, Alstonia scholaris (L) R.Br